Development of Bank Innovations - Giorgi Sulashvili; Malkhaz Sulashvili; Nino Taruashvili (Journal of Management Practices, Humanities and Social Sciences, 2020)
The aim of the study was to study banking innovative products, their classification and presentation of the quality of innovations in the banking system of Georgia. Specifically, banking services in Georgia are gradually expanding and improving. It can be said that the use of plastic cards in the banking system of Georgia is incomparable with the situation in developed countries. Thus, this study is based on a scientific study of modern and innovative methods of banking services and research on the example of commercial banks in Georgia. In this research methods of analogy, abstraction, statistical observation, system approach, and comparative analysis methods were used. The results highlight that the banks aim to reduce the risk level during the crisis and to remain the residual risk after the crises period. Global financial crises were experienced in recent years. The bank industry became the most sensitive field regarding the financial crisis. Because the risk are associated to all banking operation regardless the crisis, therefore the financial risk management should take place daily in financial institutions. The study of introduction of new banking technologies in the banking system of Georgia is important as the presence of the innovations such as plastic cards is the basis for the functioning of the country's economy.